The moderating effect of self-efficacy on the relationship between talent management practice and organizational resilience - Nelson, Alden; Agatha, Jennifer; Setyawan, Agustinus (Jurnal Siasat Bisnis, 2025)
Purpose – this study examines the moderating effect of self-efficacy (SE) on the relationship between talent management practice (TMP) and organizational resilience (OR) in electronic and electrical manufacturing organizations in Batam City.Design/methodology/approach – Data was collected by distributing questionnaires using Google Form. The sampling technique used was purposive sampling with a total sample size of 370. Testing was carried out using the PLS-SEM data analysis method in SmartPLS to test the relationship and level of significance between variables.Findings – The results showed that talent attraction (TA) and talent development (TD) did not significantly affect OR. Meanwhile, succession planning (SP) and talent retention (TR) have a significant positive effect. The moderating role of SE does not significantly affect the relationship between the four dimensions of TMP on OR.Research limitations/implications – This research only focuses on TMP in four dimensions, and on the manufacturing industry, especially in the electronics and electrical fields. Future researchers can conduct research by discussing more deeply on different dimensions and industries.Practical implications – The results provide insights and benefits for organizations to invest in effective TMP, encourage employee SE, and build a culture that supports resilience to realize OR.Originality/value – Previous research shows that OR is rarely studied in relation to TMP or SE, especially in the manufacturing industry. Given this gap, this study examines the relationship between the three.